KESAMAAN KOMUNITAS BURUNG DI KAWASAN CAGAR ALAM PANGI BINANGGA KABUPATEN PARIGI MOUTONG - n, Nurdiansyah; Labiro, Elhayat; s, Sustri (Jurnal Warta Rimba, 2019)
Indonesia has a high diversity of birds. Indonesia is known as one of the places where the world's biodiversity is concentrated, so it has been dubbed "megadiversitycountry". One of the diverse groups of animals is birds. It is estimated that 17% of all bird species in the world exist in Indonesia. The purpose of this study is to find out the similarities between bird communities in the Pangi Binangga Nature Reserve, Parigi Moutong Regency. The research method used is the path transect method. In this study, the habitats studied were primary forest, secondary forest, river and cultivation / plantation area. In the study using 1 transect in each habitat by repeating 4 times. The length of one transect line is 1,000 m. Observations were made during the active period of birds, namely in the morning at 06:00 - 10:00 WITA and in the afternoon at 15:30 - 18:00 WITA. The results of the study found 40 species of birds in four habitats namely Primary habitat, Secondary forest habitat, Cultivation Area / garden habitat, and riverside habitat, which are included in 21 families with a total number of birds is 168. In the study area there are three groups of habitat communities that are formed, namely the secondary forest group - the edge of the river - primary forest (10.47), the group of the edge of the river - primary-secondary (11.66) and the group of the edge of the river-primary-secondary-garden (14,63). Similarity index in four habitat types, namely riverbank habitat, garden habitat, secondary habitat and primary habitat that are compared, do not have similarities or are low (<50%).